Chromosome 9p terminal deletion in nine Egyptian patients and narrowing of the critical region for trigonocephaly. Issue 11 (5th October 2021) - Mohamed, Amal M.; Kamel, Alaa K.; Eid, Maha M.; Eid, Ola M.; Mekkawy, Mona; Hussein, Shymaa H.; Zaki, Maha S.; Esmail, Samira; Afifi, Hanan H.; El‐Kamah, Ghada Y.; Otaify, Ghada A.; El‐Awady, Heba Ahmed; et al.
Abstract: Background: This study aimed to delineate the clinical phenotype of patients with 9p deletions, pinpoint the chromosomal breakpoints, and identify the critical region for trigonocephaly, which is a frequent finding in 9p terminal deletion. Methods: We investigated a cohort of nine patients with chromosome 9p terminal deletions who all displayed developmental delay, intellectual disability, hypotonia, and dysmorphic features. Of them, eight had trigonocephaly, seven had brain anomalies, seven had autistic manifestations, seven had fair hair, and six had a congenital heart defect (CHD). Results: Karyotyping revealed 9p terminal deletion in all patients, and patients 8 and 9 had additional duplication of other chromosomal segments. We used six bacterial artificial chromosome (BAC) clones that could identify the breakpoints at 17–20 Mb from the 9p terminus. Array CGH identified the precise extent of the deletion in six patients; the deleted regions ranged from 16 to 18.8 Mb in four patients, patient 8 had an 11.58 Mb deletion and patient 9 had a 2.3 Mb deletion. Conclusion: The gene deletion in the 9p24 region was insufficient to cause ambiguous genitalia because six of the nine patients had normal genitalia. We suggest that the critical region for trigonocephaly lies between 11, 575 and 11, 587 Mb from the chromosome 9p terminus. To the best of our knowledge, this is the minimal critical region reported for trigonocephaly in 9p deletion syndrome, and it warrants further delineation. Abstract : Nine patients with chromosome 9p terminal deletion presented with developmental delay, intellectual disability, and dysmorphic features. We concluded that the deletion of the genes in the 9p24 region are not sufficient to cause ambiguous genitalia as six out of our nine patients had normal genitalia. Based on our study we suggested that the critical region for trigonocephaly may lies within 11.8 kb in 9p23 cytoband.